2016
DOI: 10.1016/j.cmi.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new protocol for rapid bacterial identification and susceptibility testing directly from urine samples

Abstract: The current gold standard method for the diagnosis of urinary tract infections (UTI) is urine culture that requires 18-48 h for the identification of the causative microorganisms and an additional 24 h until the results of antimicrobial susceptibility testing (AST) are available. The aim of this study was to shorten the time of urine sample processing by a combination of flow cytometry for screening and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) for bacterial id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 18 publications
1
46
1
Order By: Relevance
“…Flow cytometry is a good system for selecting samples for further analysis, and has been used to identify pathogen-positive urine for further complex testing, such as mass spectrometry analysis. Initial screening of urine samples by flow cytometry might improve clinical laboratory workflow by reducing the number of samples sent for further analysis; however, flow cytometry is only a screen for bacteriuria as it does not provide species identification or AST for definitive diagnosis 4850 .…”
Section: Detecting Utismentioning
confidence: 99%
“…Flow cytometry is a good system for selecting samples for further analysis, and has been used to identify pathogen-positive urine for further complex testing, such as mass spectrometry analysis. Initial screening of urine samples by flow cytometry might improve clinical laboratory workflow by reducing the number of samples sent for further analysis; however, flow cytometry is only a screen for bacteriuria as it does not provide species identification or AST for definitive diagnosis 4850 .…”
Section: Detecting Utismentioning
confidence: 99%
“…Inigo et al established 2 ml as the optimum volume, as it was easily manipulated in Eppendorf tubes and centrifuges (15). Zboromyrska et al used 10 ml of urine for MALDI-TOF MS and obtained higher score values of direct identification (16). In order to improve the LOD, Sánchez-Juanes et al added a pretreatment with SDS to enhance cell lysis and the release of microorganisms, and Veron et al compared different methods, concluding that previous short-culture and dual-filtration methods provided the best results (18,19).…”
Section: Urine Culture Identification Maldi-tof Ms Identificationmentioning
confidence: 99%
“…Three studies have been reported to combine MALDI-TOF MS with rapid UA (4,15,16). In order to evaluate the performance of the combination of UA and MALDI-TOF MS, only samples that were granulocyte esterase positive or nitrate reduction test positive or had bacterial counts that were greater than 500/l were combined with MALDI-TOF MS.…”
Section: Urine Culture Identification Maldi-tof Ms Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS identification of Candida species directly from blood culture bottles within 30 min was concordant with the conventional culture-based method for 95.9% of C. albicans and 86.5% of Candida non- albicans [72]. Moreover, mass cytometry, namely flow cytometry coupled with mass spectrometry, has been applied to rapidly process urine samples [77, 78]. …”
Section: Ms-based Proteomics Progresses On Microbial Identification Amentioning
confidence: 98%